Rhymes with Fighter : Clayton Yeutter, American Statesman - Weber, Joseph (Professor of journalism) (Book collections on Project MUSE., 2021)
"From a hardscrabble childhood in the Great Depression on the dusty plains of rural Nebraska, Clayton Yeutter (1930-2017) rose to work for four U.S. presidents, serving in the cabinets of two of them. His challenge, posed by one of President Ronald Reagan's aides, was this: go and change the world. As U.S. trade representative he did just that, opening the global trading arena with bold efforts that led to NAFTA, the creation of the World Trade Organization, and extraordinary growth in cross-border business. Today's global trading regime began with Yeutter. A distinguished lawyer with a doctorate in economics, Yeutter also had deep business experience leading the giant futures trading organization, the Chicago Mercantile Exchange, now called the CME Group. But he never forgot his family's farm roots, and those roots led him to another top job as President George H.W. Bush's secretary of agriculture. Yeutter's intellectual firepower, paired with an engaging personality and a midwesterner's beaming smile, made friends and found common ground with leaders and trade officials worldwide. Although a loyal GOP leader who served as counselor to a president and head of the Republican National Committee, Yeutter was a moderate who had admirers on both sides of the aisle. This is his life story."--